1999
DOI: 10.1007/978-3-540-48000-6_26
|View full text |Cite
|
Sign up to set email alerts
|

Doing More with Fewer Bits

Abstract: Abstract. We present a variant of the Diffie-Hellman scheme in which the number of bits exchanged is one third of what is used in the classical Diffie-Hellman scheme, while the offered security against attacks known today is the same. We also give applications for this variant and conjecture a extension of this variant further reducing the size of sent information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 13 publications
(18 reference statements)
0
53
0
Order By: Relevance
“…The results of that paper and some of their improvements in [15] have applications to the security of the new cryptosystem designed in [4,10].…”
Section: Remarksmentioning
confidence: 96%
“…The results of that paper and some of their improvements in [15] have applications to the security of the new cryptosystem designed in [4,10].…”
Section: Remarksmentioning
confidence: 96%
“…Section 4) based on their representations c and c k , respectively, so that the value of c k+1 follows as the trace over GF(p 2 ) of g * g k ∈ GF(p 6 ). More precisely, the owner of the private key k computes c k = T r(g k ) given c = T r(g) and k. ) is the 'smallest' (or 'largest') 1 . It follows that c k+1 is the 'smallest' possibility given the pair (c, c k ).…”
Section: Ifmentioning
confidence: 99%
“…In [1] it was shown that conjugates of elements of a subgroup of GF(p 6 ) * of order dividing φ 6 (p) = p 2 − p + 1 can be represented using 2 log 2 (p) bits, as opposed to the 6 log 2 (p) bits that would be required for their traditional representation. In [4] an improved version of the method from [1] was introduced that achieves the same communication advantage at a much lower computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The algebraic torus T d (F q ) is a (cyclic) subgroup of F × q n of order Φ d (q) for d | n, where Φ d (X) is the d-th cyclotomic polynomial. Such subgroups are recently used in several cryptographic schemes [3], [11], [16], [17], [21], which are called torus-based cryptosystems, in order to reduce the length of ciphertexts and public keys without violating the specified Manuscript received March 26, 2013. Manuscript revised July 19, 2013.…”
Section: Introductionmentioning
confidence: 99%